Analytical and computer research of stability of three layer shells, supported by stiffness ribs - Surianinov, Mykola; Yemelianova, Tetiana; Lazarieva, Dina (International Journal of Engineering and Technology, 2019)
Development of calculation model and algorithm of research of stability of three-layer cylindrical shell with light-weight aggregate, support-ed by regular transverse stiffness ribs is considered in the paper. In variational way, using the functional-action by Ostrograskiy-Hamilton, there were obtained differential equation of stability of shellâ€™s part, enclosed between ribs, and conditions along ribs lines and edges of three-layer sloping shell, supported by longitudinal stiffness ribs at simple support of edges. For external bearing layers of shell, the hy-potheses of Kirchhoff-Love were accepted. For aggregate was accepted the principle of linear change of tangential displacements along thickness. Transverse deformations were not considered. Bernoulli hypotheses were accepted for ribs. There was considered only the bent of ribs in vertical plane. Using the passage to the limit there were obtained conditions on the ribs lines without consideration of shear defor-mations in ribs. Using the theory of finite-difference equations there was obtained the stability equation for determining of parameter of critical stiffness of ribs and coefficient of critical load. Comparison of calculation results of stability of three-layer shell without ribs by au-thorâ€™s method with experimental data was performed for twenty variants of initial data.Â Â Â